Diversity of ethnomedicinal plants and traditional knowledge in Lagawa district, West Kordofan State, Sudan - Hamad, Eyman M.; Salih, Nagwa KamalL-Eldin Mohammed; Gibreel, Haytham H. (Ethnobotany Research and Applications, 2025)
Background: In Sudan, traditional medicinal plants play a critical role in healthcare, particularly in remote rural areas. This study explores the traditional medicinal plant knowledge, usage, and demographic factors influencing ethnobotanical practices in Lagawa district, West Kordofan State, Sudan. Methods: Data was gathered from 120 female and male informants, comprising 75% non-healers and 25% healers aged 20 to 79 years, using semi-structured questionnaires and group discussions. Quantitative analyses included use value (UV), informant consensus factor (ICF), fidelity level (FL), and Jaccard index (JI). Results: A total of 61 medicinal plant species from 27 families were documented, with Fabaceae being the most represented family. Trees were the dominant growth form, followed by shrubs. Fruits were associated with the highest number of medicinal species and ailments. Jaundice and diabetes were the most frequently treated ailments. Maceration was the primary preparation method, and oral administration was the most common route. Among the documented species, Adansonia digitata had the highest use value. Demographic factors significantly influenced traditional medicinal knowledge, which was predominantly transmitted through inheritance. Conclusion: The study sites are rich in traditional ethnomedicinal plants and associated knowledge. However, this cultural heritage and its biological resources face threats and require urgent conservation through systematic documentation and resource protection. Keywords: Taxonomy, Ethnobotany, Traditional medicine, West Kordofan State, Sudan